Do Investment Opportunities Matter? Evidence on the Relationship Between Profitability - Kembara Sopather (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
This study aims to analyze the effect of profitability on debt policy in mining sector companies listed on the BEI in 2021-2023 with investment opportunity set as moderating variable. This research method used quantitative methods with the secondary data in the form of financial reports. The sampling technique used purposive sampling with a total sample of 34 mining sector companies listed on the IDX in 2021-2023 that meets with sample criteria. The data obtained was analyzed using the IBM SPSS application tool version 27. Results of this research show that profitability has a negative significant effect on debt policy, while investment opportunity set could not moderate the relationship between profitability on debt policy. The set of investment opportunities owned by mining sector companies could not weaken or strengthen the relationship between the profitability owned and the company's debt policy.The higher of the profitability of a mining sector company, the more it reduces the company's debt level.